A hybrid living/organic electrochemical transistor based on the Physarum polycephalum cell endowed with both sensing and memristive properties. Issue 5 (20th May 2015) - Tarabella, G.; D'Angelo, P.; Cifarelli, A.; Dimonte, A.; Romeo, A.; Berzina, T.; Erokhin, V.; Iannotta, S.
<x xml:space="preserve">Abstract</x> A hybrid bio-organic electrochemical transistor based on the Physarum polycephalum cell, showing a multifunctional operation (transistor and memristive-like response), has been demonstrated.